Evaluating teaching practices according to the learning theories of physical education teachers for primary schools in Babylon - Shaalan, Murtaza Ali; Amir, Haider Abbas Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The teaching practices according to the learning theories of the educational cadres of teachers in primary schools in Babylon help educational institutions achieve a set of goals, so the researchers prepared this research to try to uncover the teaching practices of teachers of physical education in Babylon schools according to a comprehensive study that was adopted from the reality Existing and approved by education. Where the study included the role of educational cadres specialized in the field of schools sports and teaching practices according to learning theories and ways to apply them in primary education. The study aimed to identify the teaching practices of teachers of physical education at the primary schools , according to learning theories. And to know the extent of male and female teachers having teaching practices in physical education for the elementary stage in Babil Governorate. As for the research hypotheses, there is no significant difference between the average total teaching practices of teachers of physical education for the elementary stage, depending on the gender, experience and educational qualification variable, the descriptive approach was chosen by its survey method to suit this study. The percentage of the research sample was (79.10%) of the total number of students from the original research community.